1998
DOI: 10.1038/sj.onc.1202053
|View full text |Cite
|
Sign up to set email alerts
|

The E7 protein of human papillomavirus type 16 sensitizes primary human keratinocytes to apoptosis

Abstract: The`high risk' human papillomaviruses are associated with the development of anogenital carcinomas and their E6 and E7 genes possess immortalizing and transforming functions in several in vitro culture systems. Recently the E6 gene has also been shown to enhance the apoptosis of human mammary epithelial cells. To determine the apoptotic activity of these oncogenes in the natural host cell, we infected genital keratinocytes with retroviruses expressing either HPV-16 E6, E7, or both the E6 and E7 (E6/7) genes. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
78
2
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 28 publications
6
78
2
2
Order By: Relevance
“…Apoptosis is induced more rapidly and e ciently by TNF R1 than Fas antibody in IMR-90 cells (Figure 1d). This may also explain the di erences between this study and a published report by Richard Schlegel's laboratory that provided evidence for increased TNF-mediated apoptosis in E7-expressing keratinocytes (Stoppler et al, 1998). We have obtained similar results in keratinocytes: TNF/ cycloheximide treatment induces a relatively low level of apoptosis and the apoptotic response is much delayed compared to ®broblasts (J Basile et al, 2001, manuscript in preparation).…”
Section: Discussioncontrasting
confidence: 43%
“…Apoptosis is induced more rapidly and e ciently by TNF R1 than Fas antibody in IMR-90 cells (Figure 1d). This may also explain the di erences between this study and a published report by Richard Schlegel's laboratory that provided evidence for increased TNF-mediated apoptosis in E7-expressing keratinocytes (Stoppler et al, 1998). We have obtained similar results in keratinocytes: TNF/ cycloheximide treatment induces a relatively low level of apoptosis and the apoptotic response is much delayed compared to ®broblasts (J Basile et al, 2001, manuscript in preparation).…”
Section: Discussioncontrasting
confidence: 43%
“…This demonstrates that the expression of E6 alone, without further cellular changes, is su cient to upregulate the FGF-BP promoter in non-transformed primary human keratinocytes during their senescent growth phase. It has already been described that E7-expressing primary keratinocytes possess an increased p53 steady state level in comparison to non-HPV oncogeneexpressing keratinocytes as well as to E6-expressing keratinocytes in which p53 levels are further reduced (Demers et al, 1994;StoÈ ppler et al, 1998). As previously shown, the up-regulated p53 steady state level in E7-expressing cells led to an increase in the promoter activity of a p53-dependent promoter.…”
supporting
confidence: 59%
“…In one paper in which the entire HPV 18 sequence was present, the authors found that it conferred resistance to TNF. 71 E7, on the other hand, has been reported both to protect 72 and to sensitize 73 human fibroblasts or keratinocytes, respectively, from TNF. Our own results with the CaSki and SiHa cells (Figure 1) are consistent with the E6 dose-dependent response we have worked out in greater molecular detail in the U2OS cells, and it may be that dosage effects are important for viral proteins other than E6.…”
Section: Discussionmentioning
confidence: 99%